2009
DOI: 10.1186/1751-0759-3-13
|View full text |Cite
|
Sign up to set email alerts
|

Altered rectal sensory response induced by balloon distention in patients with functional abdominal pain syndrome

Abstract: BackgroundFunctional abdominal pain syndrome (FAPS) has chronic unexplained abdominal pain and is similar to the psychiatric diagnosis of somatoform pain disorder. A patient with irritable bowel syndrome (IBS) also has chronic unexplained abdominal pain, and rectal hypersensitivity is observed in a majority of the patients. However, no reports have evaluated the visceral sensory function of FAPS precisely. We aimed to test the hypothesis that FAPS would show altered visceral sensation compared to healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…However, the increased colonic sensitivity in idiopathic IBS is more influenced by a psychological tendency to report pain than neurosensory sensitivity (21). Irritable bowel syndrome does have a peripheral component, but the central components become more prominent as disease severity increases (22). As our patients were recruited from hospitals and not from the primary health care, we can suspect them to have a more severe disease (1).…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased colonic sensitivity in idiopathic IBS is more influenced by a psychological tendency to report pain than neurosensory sensitivity (21). Irritable bowel syndrome does have a peripheral component, but the central components become more prominent as disease severity increases (22). As our patients were recruited from hospitals and not from the primary health care, we can suspect them to have a more severe disease (1).…”
Section: Discussionmentioning
confidence: 99%
“…Centrally mediated abdominal pain syndrome (CAPS) is a recently redefined, relatively rare but severe FGID, which is defined as chronic continuous abdominal pain that is minimally related to the physiological events of eating, defecation, and menses and results in a loss of day‐to‐day functioning . While poorly understood, the mechanism of pain in these disorders is postulated to be due to central sensitization . CAPS is a challenging condition to treat with patients often presenting repeatedly with significant psychological comorbidity, multiple repeated negative investigations, and heavy socioeconomic costs including healthcare utilization and the burden of loss of working days due to illness .…”
Section: Centrally Mediated Abdominal Painmentioning
confidence: 99%
“…21 A recent study has evaluated visceral sensory function in a small sample of FAP patients in comparison to IBS and healthy controls. 22 These preliminary data demonstrated that rectal perceptual thresholds were significantly lower in patients with IBS but interestingly not in FAP, suggesting that pain reporting in FAP is less likely to be attributable to visceral hypersensitivity, which may be due to differential descending modulation in the two patient groups, thus potentially offering an objective biomarker. Wilder Smith 23 has proposed that alterations in modulatory balance may well be a unifying pathophysiological mechanism across functional bowel disorders as it can be driven by both top-down (i.e.…”
Section: Descending Modulation Of Nociceptive Pathwaysmentioning
confidence: 79%